COVID‐19 and mental health among at‐risk university students: A prospective study into risk and protective factors. Issue 1 (21st December 2021) - Koelen, Jurrijn A.; Mansueto, Alessandra C.; Finnemann, Adam; de Koning, Lisa; van der Heijde, Claudia M.; Vonk, Peter; Wolters, Nine E.; Klein, Anke; Epskamp, Sacha; Wiers, Reinout W.
Abstract: Objective: The COVID‐19 pandemic has confronted young adults with an unprecedented mental health challenge. Yet, prospective studies examining protective factors are limited. Methods: In the present study, we focused on changes in mental health in a large sample ( N  = 685) of at‐risk university students, which were measured before and during the pandemic. Network modeling was applied to 20 measured variables to explore intercorrelations between mental health factors, and to identify risk and protective factors. Latent change score modeling was used on a subset of variables. Results: The main findings indicate that (1) mental health problems increased at group level, especially depression‐anxiety and loneliness; (2) emotional support during the COVID pandemic was associated with smaller increases in loneliness and depression‐anxiety; (3) COVID‐related stress predicted increases in depression‐anxiety; (4) loneliness acted as a bridge construct between emotional support and changes in mental health. Conclusion: To mitigate the impact of the COVID‐19 pandemic on the mental health of young adults, is it recommended to focus on interventions that strengthen internal resources (stress‐regulating abilities) and reduce loneliness.